Adolescent’s Perceptions In Smoking Relapse - Putu Indraswari; Erva Elli Kristanti (HealthCare Nursing Journal, 2023)
Adolescents often experience smoking relapse in the process of smoking cessation. As individuals, adolescents' perceptions of smoking relapse influence their actions. Therefore, it is necessary to know the perceptions of adolescents who experience smoking relapse in order to determine the efforts needed to support smoking cessation for adolescents. Quantitative with cross-sectional design. The target population is teenage respondents aged 12-15 years in classes VII, VIII, and IX at SMP X Kediri. The inclusion criteria were adolescent smokers and those who had smoked. The sample size is 116 respondents and was selected by simple random. The independent variable is the perception of smoking and the dependent variable is the incidence of smoking relapse in adolescents. The instruments used were ASCQ questionnaires. Analysis of the data used to analyze the relationship using the Spearman correlation test with α = 0.05. The result shows that 116 respondents were selected to participate in this study. The relapse behavior of adolescent smoking was related to the adolescent's perception of cigarettes (p = 0.000). In Conclusion, Smoking relapse in adolescents have a significant but weak relationship with adolescent’s perception of cigarettes.